The KM processes in Malaysian SMEs: an empirical validation - Chong, Chin Wei; Chong, Siong Choy; Gan, Geok Chew (PALGRAVE MACMILLAN LTD, 2011)
This research attempts to investigate the degree of implementation of knowledge management (KM) processes in the small and medium enterprises (SMEs). The literature suggested that there are three general KM processes: construction, embodiment, and deployment. The processes are examined in detail which included the contributions of the KM process to enterprise performance. The data collected from 70 owners/managers of SMEs indicate that all the three processes are moderately implemented. However, the SMEs view KM processes as somewhat important in contributing towards better enterprise performance. The findings can be used as a guideline for SMEs to undergo a self-check and to help them rethink and reposition themselves in light of the findings. It helps SMEs to frame their KM activities to enable the creation, communication, and application of knowledge, which should allow them to drive the capability of creating and retaining a greater value onto their core business competencies. Knowledge Management Research & Practice (2011) 9, 185-196. doi:10.1057/kmrp.2011.8